Prevalence and correlates of suicidal behavior in primary care settings in Mozambique - Vasco F. J. Cumbe; Maria Nélia Manaca; Dana L. Atkins; Alberto Muanido; Leecreesha Hicks; Maria A. Oquendo; Jair de Jesus Mari; Bradley H. Wagenaar (BMC Psychiatry, 2022)
Abstract Background This study assessed the prevalence of suicidal behavior and associated risk factors in public primary health care in Mozambique. Methods The Mini International Neuropsychiatric Interview was used to evaluate suicidal behavior among 502 adults attending three Primary Health Care (PHC) settings. Results In the past month, 13% (n = 63) of PHC attendees expressed suicidal ideation, 8% (n = 40) had made a suicide plan, 4% (n = 20) had made a suicide attempt, and 5% (n = 25) reported a lifetime suicide attempt. Females had 2.8-fold increased odds of suicide plan (95% CI: 1.5, 5.5) and 3.3-fold increased odds of suicide attempt in the past month (95% CI: 1.2, 9.1). Each 10-year increase in age was associated with 0.61-fold the odds of suicide plan (95% CI: 0.38, 0.98) and 0.09-fold the odds of suicide attempt (95% CI: 0.01, 0.69) in the past month. People living with HIV (PLWHA) had 2.2-fold increased adjusted odds of past month suicide attempt (CI: 1.1, 4.1). Conclusion Suicidal behaviors are common among adults attending PHC clinics in Mozambique. Screening and linkage to effective preventive interventions are urgently needed in PHC settings. Females, younger individuals, and PLWHA are at elevated risk for suicidal behavior in PHC.